WAKAF PRODUKTIF DAN PEMBERDAYAAN EKONOMI UMAT - Kurniawan, Muhammad (ASAS, 2013)
Abstrak: Management of communal ownership productively as enableness effort of public becomes important thing of which cannot be avoided. Now various problems knocks over Indonesia resident, from problem the increasing of poorness, level of unemployment and its(the minim level of education. This thing deservedly becomes governmental attention in overcoming the problem. One of alternative which can be done is through enableness of communal ownership productively. For the shake of realized [by] it purpose of main of communal ownership to overcome this problem is needing existence of active participation from the side of non government, in this case is public. Public, especially rich faction, has ability to assist lightens grief of poor public. If public potency ( rich) this can be coordinated and is managed carefully, hence this thing can give alternative of contribution of positive solution to above mentioned poorness problem. Keyword : Wakaf Produktif, Pemberdayaan Ekonomi